2011
DOI: 10.1088/0967-3334/32/9/011
|View full text |Cite
|
Sign up to set email alerts
|

Design of a microscopic electrical impedance tomography system using two current injections

Abstract: We describe a novel design of a microscopic electrical impedance tomography (micro-EIT) system for long-term noninvasive monitoring of cell or tissue cultures. The core of the micro-EIT system is a sample container including two pairs of current-injection electrodes and 360 voltage-sensing electrodes. In designing the container, we took advantage of a hexagonal structure with fixed dimensions and electrode configuration. This eliminated technical difficulties related to the unknown irregular boundary geometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The crosstalk of the electrodes positioned around the activated current driving electrodes were -97.2 dB and -90.04 dB for cases 2 and 3, respectively. The crosstalk between the voltmeters and neighboring voltage sensing electrodes was similar to the KHU Mark1 micro-EIT system as reported by Liu et al [23]. The SNR was in the range of 59–66 dB depending on the measurement channels and the number of averaged waveform cycles (Figure 5(b)).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The crosstalk of the electrodes positioned around the activated current driving electrodes were -97.2 dB and -90.04 dB for cases 2 and 3, respectively. The crosstalk between the voltmeters and neighboring voltage sensing electrodes was similar to the KHU Mark1 micro-EIT system as reported by Liu et al [23]. The SNR was in the range of 59–66 dB depending on the measurement channels and the number of averaged waveform cycles (Figure 5(b)).…”
Section: Resultssupporting
confidence: 75%
“…For comparison our previous (KHU Mark1) system was limited as the current electrodes were placed in the middle of the array of voltage sensing electrodes [23]. The new electrode configurations and the projected image reconstruction algorithm using a logarithm formulation, instead of using the inverse solver with the least square approximation, may help to avoid a less stable solution and improve the sensitivity of the reconstructed images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A planar array of 8 × 15 electrodes was placed on each of the three sides. The voltage difference was measured between two horizontally adjacent electrodes for each current injection pattern; the last column of each row measured the voltage reference to the circuit ground [19]. There were 360 measured differential voltages along the horizontal direction for each injection current.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…To solve the difficulties in developing micro-EIT, Lee et al [18] and Liu et al [19] suggested a mathematical framework and system for a new micro-EIT method with a rectangular cuboid container that included two pairs of current injection electrodes and numerous voltage sensing electrodes, as shown in Figure 1. They applied a projected image reconstruction algorithm to produce conductivity images from the front, bottom, and back sides; they were combined to make a 3D conductivity image using a backprojection algorithm.…”
Section: Introductionmentioning
confidence: 99%